Determinants of Financial Behavior among Civil Servants: Evidence from LPP RRI Tarakan (Financial Literacy, Income, and Locus of Control) - Rizki Muhamad Arif; Andi Ayu Frihatni (Owner : Riset dan Jurnal Akuntansi, 2026)
The "SK Pawning" phenomenon has become a unique phenomenon that is increasingly being carried out by civil servants at LPP RRI Tarakan. This phenomenon is an easy solution and the safest alternative to meet financial needs. The convenience provided by the banking sector includes fast service, affordable life insurance costs, low interest rates, and status that does not have to be civil servants (PNS), but those who are still CPNS and PPPK can still pawn SK to obtain loans with a tenor of up to 15 years. Having ASN status with a stable income is a privilege to obtain loans easily and quickly. The loan funds obtained are used for various purposes, ranging from consumption, paying debts, consumptive spending to purchasing assets. The amount of income owned by civil servants can influence behavior in managing their finances. A person's locus of control can also influence how individuals manage their money. The study aims to analyze Factors Influencing Financial Conduct of Government Employees: A Case Study at LPP RRI Tarakan. In this study, the researcher applied a quantitative approach with an ex-post facto research nature. The sample used in this study was all ASN as of November 2025. Data were examined using classical assumption procedures followed by multiple regression analysis method. Based on the F-test hypothesis analysis, the results obtained showed that the F_calculated value = 30.564 > F_table = 2.751. While Adj R² = 0.573 (57.3%) and ? Income = 0.725; ? FinLit = 0.495; ? LOC = 0.414. The results the findings demonstrate that financial knowledge, earnings, and self-control orientation significantly enhance financial conduct. The existence of good financial knowledge, income and locus of control can influence ASN at LPP RRI Tarakan enabling better money management, lowering economic pressure, and enhancing quality of life.